Caracterizaçao agronomica de linhagens endogamicas s6 de milho - CESAR PRADEBON , LEONARDO; RICARDO CARVALHO , IVAN; JACOBOSKI HUTRA , DANIELI; VIEIRA LORO , MURILO; DIETTERLE SCHULZ , ADRIANO; VINICIUS UHDE FOGUESATTO , MARCOS (Salão do Conhecimento, 2021)
Agronomic Charactrization of corn s6 endogamic lines